FEATURES OF MALIGNANT NEOPLASM MORBIDITY OF THE POPULATION OF COASTAL AREAS OF THE CASPIAN SEA OF REPUBLIC - G. M. ABDURAKHMANOV; A. G. GASANGADZHIEVA; P. I. GABIBOVA (Юг России: экология, развитие)
In work are considered the basic tendencies, dynamics, territorial features and the forecast malignant neoplasm morbidity of the population of coastal areas of Daghestan republic.